Proceedings of the 15th International Workshop on Semantic Evaluation (SemEval-2021) 2021
DOI: 10.18653/v1/2021.semeval-1.73
|View full text |Cite
|
Sign up to set email alerts
|

CS-UM6P at SemEval-2021 Task 1: A Deep Learning Model-based Pre-trained Transformer Encoder for Lexical Complexity

Abstract: Lexical Complexity Prediction (LCP) involves assigning a difficulty score to a particular word or expression, in a text intended for a target audience. In this paper, we introduce a new deep learning-based system for this challenging task. The proposed system consists of a deep learning model, based on a pre-trained transformer encoder, for word and Multi-Word Expression (MWE) complexity prediction. First, on top of the encoder's contextualized word embedding, our model employs an attention layer on the input … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…For sarcasm detection, several research studies have been introduced based on fine-tuning the existing PLMs for English and Arabic languages (Ghanem et al, 2019;Ghosh et al, 2020;Abu Farha et al, 2021). El Mahdaouy et al (2021) have shown that incorporating attention layers on top of the contextualized word embedding of the PLM improves the performance of multi-task and single-task learning models for both sarcasm detection and sentiment analysis in Arabic. The main idea consists of classifying the input text based on the concatenation of the PLM's pooled output and the output of the attention layer.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For sarcasm detection, several research studies have been introduced based on fine-tuning the existing PLMs for English and Arabic languages (Ghanem et al, 2019;Ghosh et al, 2020;Abu Farha et al, 2021). El Mahdaouy et al (2021) have shown that incorporating attention layers on top of the contextualized word embedding of the PLM improves the performance of multi-task and single-task learning models for both sarcasm detection and sentiment analysis in Arabic. The main idea consists of classifying the input text based on the concatenation of the PLM's pooled output and the output of the attention layer.…”
Section: Related Workmentioning
confidence: 99%
“…The main idea consists of classifying the input text based on the concatenation of the PLM's pooled output and the output of the attention layer. This Architecture has yielded promising results on other tasks such as detecting and rating humor, lexical complexity prediction, and fine-grained Arabic dialect identification (Essefar et al, 2021;El Mamoun et al, 2021;El Mekki et al, 2021b).…”
Section: Related Workmentioning
confidence: 99%
“…El Mamoun et al [17] introduced a new deep learning-based system for this challenging task. The proposed system consisted of a deep learning model based on a pre-trained transformer encoder for word and Multi-Word Expression (MWE) complexity prediction.…”
Section: Related Workmentioning
confidence: 99%
“…Each classification layer is feed with the concatenation of the task attention output and the [CLS] token embedding. This model has shown effective performances in many NLP tasks, including dialect identification, sentiment analysis and sarcasm detection for the Arabic language [7,8], humor detection and rating, as well as lexical complexity prediction in English [17,18]. The single-task counterpart of MT_ATT is denoted by ST_ATT.…”
Section: Deep Learning Modelsmentioning
confidence: 99%